Temporal trends in stillbirth in the United States, 1992–2004: a population‐based cohort study. (27th May 2014) - Zhang, X; Kramer, MS
<x xml:space="preserve">Abstract</x> Objective To examine temporal trends in stillbirth and its risk factors in the United States (US), and to assess the contribution of labour induction and caesarean delivery to the stillbirth rate. Design Population‐based cohort study based on linked birth‐infant death and fetal death data files from the US National Vital Statistics System. Setting Complete data were available for 44 states and the District of Columbia. Population or Sample Singleton births from 1992 to 2004. Methods We assessed changes in stillbirth rates from 1992–1994 to 2002–2004 before and after adjustment for changes in maternal characteristics including maternal age, education, smoking, and medical risk factors, using Cox regression models. We also carried out an ecological study, using states as the units of analysis, to assess the impact on the stillbirth rate of increasing induction and caesarean delivery. Race‐specific subgroup analyses were performed and included non‐Hispanic Whites and non‐Hispanic Blacks. Main outcome measure Stillbirth rate. Results The stillbirth rate among non‐Hispanic White singleton births decreased 11.5% from 1992–1994 (5.2 per 1000) to 2002–2004 (4.6 per 1000). After adjustment for maternal risk factors, the hazard ratio (HR) for 2002–2004 was 1.01 (0.99, 1.03) for gestational age (GA) ≤39 weeks, but 0.92 (0.86, 0.99) at 40 or more weeks. The ecologic analysis revealed a nonsignificant negative correlation of −0.17 (−0.44, 0.13) between state‐level changes in stillbirth at GA ≥40 weeks and labour induction. A nonsignificant positive correlation of 0.23 (−0.07, 0.49) was observed between changes in stillbirth at all GAs and caesarean delivery and did not differ at GA ≤39 versus ≥40 weeks. Results were similar among non‐Hispanic Blacks. Conclusions Changes in maternal risk factors explained the reduction in stillbirth at GA ≤39 weeks but not at ≥40 weeks. The rise in labour induction and caesarean delivery rates did not explain the reduction in stillbirth ≥40 weeks of gestation.